[2 + 2] Cycloaddition Reactions of Butadienyl Ketene with 1, 4‐Diazabuta‐1, 3‐dienes: Synthesis of Functionalized Butadienyl‐4‐iminomethyl‐azetidin‐2‐ones and Butenylidene‐butadienyl‐[2, 2′‐biazetidine]‐4, 4′‐diones. (28th August 2015) - Bains, Deepak; Kumar, Yogesh; Singh, Prabhpreet; Bhargava, Gaurav
Abstract : The reactions of butadienylketene with variety of 1, 4‐diazabuta‐1, 3‐dienes are studied. The reactions resulted in the formation of previously unknown functionalized cis butadienyl‐4‐iminomethyl‐azetidin‐2‐ones and butenylidene‐butadienyl‐[2, 2′‐biazetidine]‐4, 4′‐ diones. Butadienyl ketene reacts in[2+2] cycloaddition fashion with both iminic portion of 1, 4‐ diazabuta‐1, 3‐dienes and competitive [4+2]cycloaddition reaction of 1, 4‐diazabuta‐1, 3‐dienes as 4π component with butadienyl ketene as 2π component are not observed. Abstract :